MANAGEMENT OF CRITICALLY ILL PATIENT FOLLOWING MULTIPLE ABDOMINAL TRAUMA WITH MASSIVE HEMORRHAGE : CASE REPORT - Ikhwan Nur, Muhammad; Rismawan, Budiana (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Most patients with severe abdominal trauma with massive bleeding require intensive care. On most occasions patients will be admitted to Intensive Care after surgery and require close monitoring of vital signs. Care in the ICU will focus on monitoring and supportive measures. The management of bleeding in critically ill patients is a dynamic and complex process. In addition, transfusion strategies during bleeding may involve several concurrent strategies to monitor coagulopathy, transfusion of blood products, and administration of drugs to correct coagulation disorders. Case report : A 48-year-old male was admitted to the ICU after a traffic accident. The patient came to the emergency room with bleeding shock and fluid resuscitation was performed to restore MAP 60 mmHg. Damage control surgery and massive transfusion were performed to save the patient. After the first operation, the patient returned to shock, producing 1500 cc hepatal and subphrenic drain in 3 hours. Re-laparotomy abdominal re-breaking surgery was performed again with additional packed red blood cells (PRBCs), Fresh Frozen Plasma (FFP) and platelet transfusion during surgery. Post-second surgery, the patient's hemodynamics were stable and vasopressor drugs could be weaned. The patient was admitted to the ICU with invasive monitoring and mechanical ventilator. After the 4th day, the patient experienced volume overload and pulmonary edema. Furosemide was given to eliminate fluid accumulation. The patient was extubated on day 6 and moved to the ward on day 7. Discussion : In cases of intra-abdominal trauma, Focused Assessment With Sonography For Trauma (FAST) examination can be performed quickly so that the decision to perform surgical resuscitation can be made immediately. Damage control surgery is performed in conditions where bleeding cannot be controlled through definitive procedures. Abdominal packing can be performed to prevent further bleeding while waiting for hemodynamic stabilization and coagulopathy in the ICU. Giving massive transfusions such as PRBCs, FFP and platelets according to protocol prevents the occurrence of lethal triad in massive bleeding patients. On the other hand, massive transfusion also brings side effects and complications such as volume overload, electrolyte disturbances, acidosis, transfusion reactions and infection in patients. The administration of blood and fluid transfusion in post-traumatic patients in the ICU must be done carefully to prevent these complications. Conclusion : In cases of intra-abdominal trauma patients with massive bleeding, early diagnosis, damage control surgery and proper management of massive transfusion are the management that must be done to save the patient.